Global Trends in Research on Microplastic Contamination and River Water Quality: A Bibliometric Review - Nisa Nur Agistni Eriana; Nia Kania; Meitria Syahadatina Noor; Eko Suhartono; Herawati Herawati (Malahayati Nursing Journal, 2024)
ABSTRACT This study aims to analyse global trends in research related to microplastic contamination and river water quality using a bibliometric approach. Microplastics have become one of the most pressing environmental issues in recent decades, mainly due to their significant impact on aquatic ecosystems and potential harm to human health. Along with the increasing attention to this issue, the scientific literature related to microplastics and river water quality has grown rapidly. However, a thorough understanding of the distribution of research, relationships between topics, as well as potential research gaps is still needed to direct future research more effectively. This study used a literature search method through the Publish or Perish app, with keywords including "microplastics," "water quality," "water pollution," "microplastic contamination," and "river." The search was conducted from 2014 to 2024, resulting in 50 relevant articles for further analysis. The data obtained was then processed using VOSviewer to map and visualise the bibliometric network, identify key clusters, and evaluate the temporal progression of these research topics. The resulting visualisations, including network visualisation, overlay visualisation, and density visualisation, provide deep insights into how key terms are connected and evolve in the literature. The analysis showed that research on microplastics in the context of rivers and water quality is heavily dominated by a few key terms such as "microplastic," "river," and "water," indicating the high level of scientific attention on this topic. In addition, it was found that research often focuses on the distribution of microplastics, physicochemical parameters of water, and sources of contamination. However, there are some significant research gaps, especially related to the effect of salinity on microplastic distribution, the accumulation of microplastics in river sediments, and the role of wastewater treatment plants in preventing the spread of microplastics to aquatic ecosystems. The conclusion of this study is that despite significant progress in understanding the distribution and impacts of microplastics, many aspects still require further research. In particular, research on the long-term impacts of microplastics and their interactions with other environmental components should be further enhanced. The findings are expected to provide guidance for future researchers to explore under-explored areas and contribute to better environmental management. Keywords: Microplastic, Water Quality, River Pollution, Bibliometric Analysis, Environmental Research